Analisis dan Perbaikan Proses Bisnis Menggunakan Metode Business Process Improvement (BPI) Framework (Studi Kasus Bidang Pengembangan Produk Pariwisata Dinas Pariwisata Kota Batu) - Indra Fahrizal; Ismiarta Aknuranda; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Tourism Product Development Division of Batu City Tourism Office has 6 business processes; there is Business Travel Certification for Hotel & Restaurant, Services & Tourism Facilities Data Collection, Coordination in Tourism Village Acceleration, Coordination in Tourism Product Development, and East Java Tourism Awards & Characteristically Food Festival, and Tourism Village Development Study. In running the business process there is a trouble such as deadline business data target that not achieved so that it will holding up the next implementation process, administration still paper-based that usually cause losing data. So that must be analysis and business modeling process that can make the process more effective and efficient. In this research used Business Process Improvement method from phase 1: organizing for improvement until phase 3: streamlining. After the business process has been corrected with automation technic and elimination process it come with a result from simulation, there are the lowest time different is in recommendation business process, the making of the final report decrease as much as 1 day 6 hours 10 minutes or 14,70%, and the highest time different is in the process of Services & Tourism Facilities Data Collection that decrease as much as 12 days 5 hours 20 minutes or 56,07%. So, can be concluded that the recommendation business process more efficient because have little time completion compared to business process that runs now in Tourism Product Development Division of Batu City Tourism Office